THE SYNTACTIC BEHAVIOUR OF THE SECOND VERB (V2) IN BALINESE SERIAL VERBS - Ni Luh Ketut Mas Indrawati; Ida Ayu Made Puspani (Linguistik Indonesia, 2022)
The title of this study is the syntactic behavior of the second verb (V2) in the Balinese serial verbs and it aims at investigating the types of verbs composing the Balinese serial verbs and analyzing the syntactic behavior of the V2. The theory applied in identifying the Balinese serial verbs is the theory of typology by Van Staden and Ger Reesink (Senft, ed., 2008), and the theory of complement and adjunct by Kroeger (2005) is used in analyzing the syntactic behavior of the V2. This research is classified as a descriptive-qualitative study. The data supporting the analysis was collected from written Balinese texts in the Balinese short stories. The result of the analysis showed that the Balinese serial verbs were formed by V1 stative-V2 intransitive, V1 intransitive -V2 stative, V1 intransitive -V2 transitive active, V1 active transitive -V2 active-transitive, or stative or intransitive, passive-active-transitive, active transitive-passive, passive-passive. Syntactically the V2 could be either complement or an adjunct of the V1.